Climate niche mismatch and the collapse of primate seed dispersal services in the Amazon. (July 2020) - Sales, Lilian; Culot, Laurence; Pires, Mathias M.
Abstract: Animal-plant interactions are threatened by ongoing climate change, deforestation, and defaunation. The disruption of biotic interactions leads to loss of ecosystem services but estimates of the magnitude of reductions are rarely available. Using a seed disperser primate community in the Amazon as study case, we forecast the magnitude of seed dispersal services to be lost as function of the future redistribution of species. In the most likely scenario, our projections indicate average contractions of 56% (23 to 100% reduction) on the suitable areas for the studied primates. As result, we found billions of seeds of a model tree ( Manilkara bidentata ) might fail to be dispersed by this primate community on each fruiting season. Primate contribution to seed dispersal was, however, uneven among species, highlighting the endangered large-bodied woolly monkey Lagothrix cana as a keystone disperser. That species alone was responsible for about 64% of all Manilkara seeds dispersed in the present and up to 71% in the future. Niche mismatch will, however, lead to 37% of the future plant distribution not being able to host its second top disperser (the tufted capuchin Sapajus apella ), exacerbating losses on potential seed dispersal. Our projections indicate that seed dispersal in tropical forests might be hampered by global changes, even if defaunation by poaching is controlled. The forecasted magnitude of loss in seed dispersal services is alarming and may have been overlooked in conservation assessments. In a similar manner, niche mismatch and disruption of biotic interactions will likely impair ecosystems functions and resilience worldwide. Graphical abstract: Unlabelled Image